Correlation between Tp-Te Interval and Myocardial Blush Grade Value in Anterior ST Elevation Myocardial Infarction Patient - Rio Probo Kaneko; Erika Maharani; Nahar Taufiq (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2018)
Background: Clinical manifestations of coronary herat disease (CHD) may be an ST-Elevation Myocardial Infarction (STEMI). In STEMI condition, there is a metabolic disorder and ion exchange disturbance which causes dispersion of transmural repolarization, as well as micro coronary circulation disturbance involving mechanism of microvascular dysfunction. The Tp-Te interval is an electrocardiogram paramener that could be described as the transmural dispersion of repolarization. Assessment of Myocardial Blush Grade (MBG) is a coronary angiography densitometry method that can be used to assess microvascular dysfunction. This study aims to examine the correlation between Tp-Te interval and MBG in anterior STEMI.Methods: The research desgin is cross sectional. Data were taken consecutive from August to November 2017. The Tp-Te interval assessment was performed on the basis of an electrocardiogram record from the subjects. The MBG value assessment was performed using a Quantitative Blush Evaluator (QuBE) computer program based on coronary angiography. The Tp-Te interval is divided into 2 groups: Tp-Te interval > 94 ms and Tp-Te interval ≤ 94 ms. The MBG values are divided into 3 groups: MBG QuBE 1, MBG QuBE 2 and MBG QuBE 3. The assessment of Tp-Te interval and MBG value was performed by observer in intra-observer which were acknowledged based on Kappa and blindness conformity test results against patient clinical data. Pearson correlation test was used to analyze the correlation between Tp-Te interval and MBG value, while logistic regression test was used for multivariate test.Results: Of the total 32 study subjects, there were 23 subjects with Tp-Te interval >94 ms and 9 subjects with Tp-Te interval ≤94 ms. There was a negative correlationwith moderate strength between the Tp-Te interval and the MBG value in the anterior STEMI patients (r =-0.501, p =0.004). There was a prevalence ratio of 4.304 between Tp-Te interval >94 milliseconds against MBG QuBE 1 (95%CI: 1.264-14.658, p <0.001). Multivariate tests showed Tp-Te intervals consistently as independent risk factors for MBG values in subjects with anterior STEMI.Conclusion: There is a negative correlation with moderate strength between the Tp-Te interval and the MBG value in the anterior STEMI patients.